Prevalence of undiagnosed hypertension and risk assessment using a validated survey in community-based screening in Amman, Jordan - Anas Khaleel; Malak Al-Quaiti; Sara Istaitiya; Abhijit V. Kshirsagar; Heejung Bang (PLoS ONE, 2026)
Background and objectives The rising incidence of hypertension in Jordan has contributed to high rates of associated morbidity/mortality and increased societal costs. Hypertension affects approximately 30% of Jordan’s adult population. This study assessed the prevalence of undiagnosed hypertension through blood pressure measurement and evaluated future hypertension risk using a validated survey in a community setting. The survey instrument incorporates demographic and clinical factors to predict the likelihood of hypertension development within a nine-year timeframe. Methods We conducted a cross-sectional local community screening in Amman, Jordan (Sept 2022-Sept 2023). Trained university pharmacy students had measured blood pressure and distributed a validated 9-risk predictors questionnaire to adults without diagnosed hypertension during a single visit. Participants were categorized using American Heart Association criteria. Results Among 932 adult participants of the study, approximately 57% were female, 34% were overweight, 16% were obese, and 5.3% were extremely obese. Risk factors included current smoking (38%), diabetes mellitus comorbidity (8%), family history of hypertension (61%), and insufficient exercise (62%). Systolic readings were classified as elevated (45%), stage 1 (15%), or stage 2 (5.5%). Diastolic readings had stage 1 (42%) or stage 2 (7.6%). Participants with risk scores ≥17 (n = 39) were those who had current hypertension (BP ≥ 140/90 mmHg). Those were classified as high-risk based on established cutoffs. Conclusion Our community screening revealed a high prevalence of undiagnosed hypertension (20.6%) and identified a substantial proportion at high risk for future hypertension. The risk assessment tool showed good screening ability to reveal the participants’ hypertension status, supporting its utility for risk stratification in resource-limited settings. Moreover, our validated risk tool effectively classified between those with and without current hypertension and identified individuals needing intensive preventive interventions. This dual approach of BP measurement and risk assessment may guide targeted screening intervals and preventive interventions in Jordan and similar settings.